Concept Analysis of Nursing Triage Accuracy Using the Emergency Severity Index: A Walker and Avant Approach - Ni Luh Putu Inca Buntari Agustini; Santika Wiadnyana; I Gusti Lanang Suta Jayendra; I Putu Purnamayasa; Ni Made Sari Utami; Putri Dewi Utari; Ni Wayan Sukerti; Ni Luh Dwi Indrayani; I Gede Putu Darma Suyasa (Universitas Airlangga, 2026)
Introduction: Emergency nursing triage requires accurate and consistent decision-making to ensure patient safety and appropriate care prioritization. The Emergency Severity Index (ESI) is widely used as a five-level triage framework; however, conceptual ambiguity remains regarding nursing triage accuracy in its application. This study aimed to analyze the concept of nursing triage accuracy using ESI through Walker and Avant’s concept analysis method. Method: This study used Walker and Avant’s concept analysis approach. Literature from PubMed and ScienceDirect published between 2020 and 2025 was reviewed to identify concept uses, defining attributes, antecedents, consequences, empirical referents, and illustrative cases. Results: Nursing triage accuracy using ESI was identified as a multidimensional concept. Its defining attributes include clinical judgment, consistency in decision-making, accurate patient prioritization, reliability of clinical decisions, and patient safety-oriented decision-making. Key antecedents include nurses’ competence, emergency nursing experience, ESI training, standard operating procedures, adequate facilities, and healthcare system support. Consequences include improved patient safety, reduced undertriage and overtriage, shorter waiting times, efficient resource allocation, and improved emergency nursing care quality. Conclusions: Nursing triage accuracy using ESI is defined as the nurse’s ability to make accurate, consistent, reliable, and patient safety-oriented triage decisions by assessing patient acuity, recognizing clinical urgency, and prioritizing care appropriately within the ESI framework.